Job Embeddedness: Factors and Barriers of Persons with Disabilities - Lashari, Dr Tahira Anwar; Lashari , Sana Anwar; Lashari , Saima Anwar; Nawaz, Sarwat; Waheed, Zahra; Fatima, Tehreem (Journal of Technical Education and Training, 2022)
Addressing the employment problems facing persons with disabilities (PWDs) is complicated as it depends on the presence of certain core values of others such as non-discrimination, in order to recognise their capabilities. PWDs can engage in many economic activities in Pakistan, however, in general, the employment rate for PWDs is relatively low. Qualitative research was used to ascertain insight into a central phenomenon. Data was collected through interviews and observation from five different workplaces through purposive sampling, and a thematic analysis technique was used to analyse the data. The participants were 50 years or less and were mainly men who had worked with people with disabilities for 2-5 years The study revealed that the major issue of employers was their perception that PWDs were less productive than those employees without a disability. The study reported that the responsibility to create a positive image and to think inclusively about PWD’s working capabilities was the responsibility of the persons with disabilities.